2021
DOI: 10.1002/pbc.29418
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial care providers’ perspectives: Barriers to implementing services for siblings of children with cancer

Abstract: Background Siblings of children with cancer are at increased risk for poor long‐term psychosocial outcomes. The standard of psychosocial care in pediatric oncology calling for sibling support is not routinely implemented, often leaving siblings with unmet psychosocial needs. Barriers to implementing the sibling standard may exist at multiple levels. This study addresses research gaps regarding multilevel barriers to supporting siblings at the health care system, oncology center, and family levels. Procedure Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Previous work has identified that siblings of children with cancer are at risk for poor adaptation, difficulties in school, and altered relationships with members of their social networks [ 4 , 6 ]. Barriers to supporting siblings have also been identified [ 29 , 30 ], and structured support may not be available to many siblings. COVID-19 has further limited access to supportive services [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has identified that siblings of children with cancer are at risk for poor adaptation, difficulties in school, and altered relationships with members of their social networks [ 4 , 6 ]. Barriers to supporting siblings have also been identified [ 29 , 30 ], and structured support may not be available to many siblings. COVID-19 has further limited access to supportive services [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gap between the Sibling Standard and current care practices must be viewed in light of emerging research on multisystemic interacting barriers to sibling psychosocial care. For example, reliance on parent report is understandable given providers’ limited time and access to siblings 27 . Yet, due to parents’ own limited time and attentional resources, they are often unaware of how siblings are coping with cancer, and thus may be unable to provide accurate information about sibling psychosocial risk 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 30 (47%) expressed interest in participating. Three were subsequently lost to contact, resulting in a total of 27 providers (42%) who provided data 27 . The resulting sample was heterogeneous across provider discipline, center size, institution type, and level of sibling support (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Siblings commonly report unmet psychosocial needs (O’Shea et al, 2012; Patterson et al, 2017). Although supporting siblings is now a standard of care in pediatric oncology (Gerhardt et al, 2015), this standard is not being routinely met (Scialla et al, 2018) due to a multitude of healthcare delivery barriers such as billing/documentation challenges and staff shortages (Brosnan et al, 2021). Historically, sibling research has been challenged by limited awareness of siblings’ needs across families and healthcare systems, methodological concerns including small sample sizes, and few funding opportunities (Long et al, 2015b).…”
mentioning
confidence: 99%